Institutional Peiformance in Housing Finance - Bhalla, Ashwani Kumar (Gyan Management Journal, 2008)
Housing Finance Industry in ndia has shown unprecedented arowth in the last ten years. There are large numbers of new pl ay ers in the market meeting the customer’s housing finance requirements. In the post liberalization period many developments has taken place in the housing finance sector. The present paper is an attempt to analyze the institutional performance in disbursements of Housing finance in lhe post liberalization period and to tudy how the different players in the field of housing finance are evolving in India in the development and growth of housing finance sector. Simple regression analysis of Curve estimation with linear method to compute R-Square (Co-efficient of determination), bl (slope of regression line) has been used with AN OVA results to determine the contribution of various institutions in the housing finance sector.